Contribution of Traditional Industry and Crafts to Local Development Case Study of the Traditional Chamber of Industry and Crafts of the State of Tiaret in 2012/2022 - gherbali, hadjer nouwara; Benelhadj djelloul , Yacine (Journal of Excellence for Economics and Management Research, 2024)
The Algerian State, like other developing countries, seeks to achieve local development by pursuing a number of measures and adopting various strategies, including the development of various sectors. In the same context, the State has directed its attention to the traditional industry and crafts sector in promoting economic activity and the establishment of enterprises, in view of the high demand for it because of its simplicity and ability to create jobs. Through this study, we aim to determine the extent to which the traditional industry and crafts sector has contributed to local development by highlighting the experience of the Tiaret State Chamber of Traditional Industry and Crafts. In this study, we have concluded that the traditional industry and crafts sector is important as a reliable sector in improving the living, economic and social conditions of the local population. This is what the Tiaret State Chamber of Traditional Industry and Crafts aspires to.